Pengaruh Kadar Hb dan Paritas dengan Kejadian Intra Uterine Fetal Death (IUFD) di RSUD Arifin Achmad Pekanbaru. - Ani Triana (STIKes Hang Tuah Pekanbaru, 2012)
IntraUterineFetalDeath(IUFD) is adead fetusin the wombweighing â‰¥500 gramsordeath ofthe fetus in thewombat 20 weeksormore. Data obtainedfrom theMedical RecordsGeneral HospitalArifinAchmadPekanbarufrom 2009 to2011 toincreasethe incidence ofIUFD. In 2009the proportion ofthe incidence ofIUFD3.6%of2929deliveries.In 2010the proportion ofIUFDincidenceincreased 4.2% from 2989deliveries. In 2011the proportionincreased 4.4% from 2856deliveries. The purposeof researchisknownrisk factorin theincidence ofIUFDGeneral Hospital Arifin Achmad Pekanbaru2010-2011.The designstudy is acase-control study(casecontrol study). The case ofthedead fetusin the wombwere born tomothersin General Hospital Arifin Achmad Pekanbaruin 2010-2011periodJanuary 2010-December 2011 andthe controlinfants born tomotherslivingin General Hospital Arifin Achmad Pekanbaru2010-2011periodJanuary 2010-December 2011 .The resultsof women havingHb<11 g% higher risk of havingIUFD3 times(95% CI1.9 to 4.9) than those whohave theHb levelâ‰¥11 g%, mothers withparity0 and> 4 moreriskybearwithIUFD1.5 times(95% CI1 to 2.1) compared towomen whohadparity1-4. The conclusionthatthe independentvariablesthat havea causal relationshipwith the incidence ofIUFDishemoglobinandparity. Adviceisintended forhealth professionalsactive inproviding information, forGeneral Hospital Arifin Achmad Pekanbaruneed tobe active inimplementingAMP, andfor pregnant womenand families that participate inprenatal careandfamily planning